2018
DOI: 10.1016/j.conbuildmat.2017.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated cellulose and cellulosic pulp for reinforcement of the extruded cement based materials

Abstract: The high specific surface area of NC improves the fiber-matrix bonding. The NC improves the stress transfer when the composite is subjected to load. At 28 days the hybrid composite presents a higher modulus of rupture. In the hybrid composite, the NC acts as nanoreinforcement after accelerated ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 43 publications
2
27
0
7
Order By: Relevance
“…The results achieved by Urrea-Ceferino et al [36] show that accelerated carbonation curing reduces matrix alkalinity and mitigates the cellulose degradation in cementitious composites. Table 1 presents the results of the study developed by Correia et al [82]. The authors studied the effect of hybrid reinforcement (bamboo nanofibrillated cellulose + bamboo pulp) in the performance of carbonated cement composites produced by the extrusion process in comparison to carbonated composites reinforced with only bamboo pulp, at 28 days and after 200 cycles of immersion and drying.…”
Section: Accelerated Carbonation Curing For Cement-4 Based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results achieved by Urrea-Ceferino et al [36] show that accelerated carbonation curing reduces matrix alkalinity and mitigates the cellulose degradation in cementitious composites. Table 1 presents the results of the study developed by Correia et al [82]. The authors studied the effect of hybrid reinforcement (bamboo nanofibrillated cellulose + bamboo pulp) in the performance of carbonated cement composites produced by the extrusion process in comparison to carbonated composites reinforced with only bamboo pulp, at 28 days and after 200 cycles of immersion and drying.…”
Section: Accelerated Carbonation Curing For Cement-4 Based Compositesmentioning
confidence: 99%
“…The results indicate that the nanofibers present a higher contribution to delay the onset of crack propagation and its potential to act as stress transfer bridges in the nanocracking, mainly after 200 cycles of immersion and drying. The results of flexural stress (MOR) and energy of fracture shows that after accelerated aging the nanofibrillated cellulose preserved partially its ability to form bonds, once the fibers have remained undamaged [82]. Thus, the potential of the use of nanofibrillated cellulose as a reinforcing element of cementitious materials to increase the mechanical performance of these materials was assessed.…”
Section: Accelerated Carbonation Curing For Cement-4 Based Compositesmentioning
confidence: 99%
“…NFCs contain crystalline and amorphous regions and they have diameters in the range of 5-60 nm and lengths of several hundred nanometers (Klemm et al 2011;Klemm et al 2018). NFCs have high specific surface area, which increase the interaction of the fibers with the matrix promoting the higher mechanical strength of the reinforced composites (Correia et al 2018a;Correia et al 2016;Ardanuy et al 2012a;Ardanuy et al 2012b). According to Correia et al (2018b) NFC contribute to the increase of the physical and chemical adhesion, friction and mechanical anchorage with the matrix with respect pulps, induced by its high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus and pinus pulp are traditionally used in the producing of commercial fibercement products by the Hatschek process, but some studies have shown that bamboo pulp and NFCs also have potential to be used as reinforcement for these cement-based materials (Correia et al 2018a ;Li et al 2017;Xie et al 2015;Correia et al 2014;Rodrigues et al 2010;Rodrigues et al 2006;Coutts and Ni 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, under accelerated aging by carbonation, the composites with or without nanofibers do not reduce the mechanical performance due to the lower alkalinity provided by the accelerated carbonation. Therefore, the nanofibrillated cellulose appears to be a promising material to be used as nano-reinforcement of the extruded hybrid cement-based composites [25]. Moreover, PVA and macro-synthetic fibers offer a good performance in terms of bonding strength with the cement matrix thanks to its hydrophilicity [26,27], which compensates for the potential of cracking occurring in the matrix.…”
Section: Introductionmentioning
confidence: 99%